Sistem Akuisisi Data dan Monitoring Parameter Cuaca Berbasis Mikrokontroler - Asruddin Basri; A. Irmayani Pawelloi; Muhammad Zainal (Fakultas Teknik Universitas Muhammadiyah Parepare (FT-UMPAR), 2025)
Monitoring weather parameters in agricultural fields is essential for improving cultivation efficiency and supporting data-driven decision-making. Farmers often face limited access to real-time microclimate information, highlighting the need for an autonomous and accurate data acquisition system that can operate reliably in the field. This study aims to design and evaluate a sensor-based weather monitoring system that measures temperature, humidity, light intensity, and rainfall conditions, with an emphasis on supporting precision agriculture in rural areas. Field testing was carried out at the Paccoka agricultural site in Watang Suppa Village, where 15 sets of measurements were collected using digital sensors and an RTC module. The results indicate high sensor accuracy, achieving 97.92% for temperature, 94.03% for humidity, and 96.56% for light intensity, while the rain sensor consistently detected surface moisture variations based on incremental water droplets. The developed system demonstrated stable performance and effectively captured real-time microclimate dynamics, making it suitable for implementation as an IoT-based environmental monitoring solution in agricultural applications.